Estudo da emissão de poluentes por veículos oriundos de um polo gerador de viagens: a estimativa da rota ambiental para ônibus intermunicipais na cidade de Uberaba, MG - Oliveira, Luis César de (2014)
This study analyzed the emission of pollutants caused by vehicles, both in a bus station as on the route that vehicles use to their destinations. It was used a theoretical basis and a commercial software, TSIS, that provides the mass discharge of major pollutants emitted by intercity and interstate buses using the bus station of Uberaba, MG. It was simulated the discharge of pollutants emitted by vehicles and it was provided subsidies to studies of routes in relation to the generation of air pollutants due to the concentration of vehicles in trip generation hubes. There were simulated four routes and it was founded the one with emmited the lesser air pollution quantity, which was considered as the environmental route. It is expected to contribute to the city and state agencies, which are in charge in taking an efficient decision to control the vehicular pollution, because automotive gases can cause damages on the population health and on the environment.